Nonautonomous differential equations of alternately retarded and advanced type - Qiong Meng; Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
We obtain a solution formula of the differential equation x˙(t)+a(t)x(t)+b(t)x(g(t))=f(t). At the same time, we study its oscillation and asymptotic stability properties.